The Relationship of Breastfeeding Patterns with The Nutritional Status of Infants 6–24 Months - Yuli Astutik, Reni; Nining Istighosah; Suci Anggraeni; Stevani Basuki Putri; Martina Marlince Walla (Journal for Quality in Public Health, 2024)
Babies who are exclusively breastfed will get all the advantages of breast milk and maximum nutrition. On the other hand, the incidence of malnutrition in the future is largely determined by breastfeeding patterns. The aim of this research is to determine the relationship between breastfeeding patterns and the nutritional status of babies aged 6–24 months at the Islamic Boarding School I Community Health Center, Kediri City. This study used a cross-sectional design. The research population was mothers who had babies aged 6–24 months at the Pesantren I Health Center in Kediri City in August–October 2023, for a total of 150 babies. The research sample consisted of several mothers who had babies aged 6–24 months at the Pesantren I Health Center in Kediri City who met the inclusion and exclusion criteria. There were 110 respondents. The research instrument for assessing breastfeeding patterns uses a questionnaire, while nutritional status is assessed using height and weight measurements. Data analysis used the Spearman rho statistical test. Half of the mothers had a pattern of predominant breastfeeding, namely 50%. Based on nutritional status, undernutrition 28.2%,. The Lambda test results show p = 0.016, meaning that there was a relationship between breastfeeding patterns and the nutritional status of children aged 6-24 months. The magnitude of the correlation was 0.152 which indicates the correlation very weak category. Breast milk given exclusively during the first 6 months of life can provide sufficient nutrition for the baby's growth and development.